Durability of lightweight aggregate concrete containing oil palm ash (OPA) - Wan Nur Amierah, Wan Mustafa (2018)
In Malaysia, the industry of palm oil has grown rapidly throughout the years causing an immense production of waste that will surely affect the environment negatively. The production of construction material from natural resources such as cement has produced an excessive amount of unnecessary gas into the air causing a blunt greenhouse effect on the environment. Oil Palm Ash (OPA) as one types of palm oil industrial wastes – can be easily obtained, were used in the research that in order to help in overcoming these problems. In regard of its uncertain performance as a content of lightweight concrete, an investigation in terms of durability against acid and sulphate attacks and water absorption were also made. Five series of 0%, 10%, 20%, 30% and 40% of OPA content lightweight concrete with the same mix proportioning of (100X100) mm2 cube size were prepared. The specimen with 0% content of OPA was set as the control specimen of the investigation. These lightweight concrete specimens were then cured for 28 days – 7 days in water and the rest will be air cured. Losses of mass was observed in regard of acid and sulphate resistance test. Strength deterioration in regard of acid resistance test. While, in water absorption rate, the water absorption test were necessarily observed. The distinct result obtained concluded that with the increasing content of OPA, the specimens become susceptible to loss mass as compared to its original mass and deteriorate in strength. The water absorption rate observed also increase as OPA content increases. It is concluded that, all these negative effects on the specimens were only observed when the content of OPA is too much and exceeded the optimum content of OPA.